Search for a Vectorlike Quark With Charge 2/3 in T+z Events From Pp Collisions at ?s=7tev - Karapınar, Güler; Karapınar, Güler; Demir, Durmuş Ali; Demir, Durmuş Ali (American Physical Society, 2011)
A search for pair-produced heavy vectorlike charge-2/3 quarks, T, in pp collisions at a center-of-mass energy of 7 TeV, is performed with the CMS detector at the LHC. Events consistent with the flavor-changing-neutral-current decay of a T quark to a top quark and a Z boson are selected by requiring two leptons from the Z-boson decay, as well as an additional isolated charged lepton. In a data sample corresponding to an integrated luminosity of 1.14fb -1, the number of observed events is found to be consistent with the standard model background prediction. Assuming a branching fraction of 100% for the decay T→tZ, a T quark with a mass less than 475GeV/c 2 is excluded at the 95% confidence level. © 2011 CERN.
Keywords: High energy physics; Bosons; Tellurium compounds; CMS detectors